ANALISIS DAMPAK EKONOMI KEBERADAAN DESA WISATA KEMANTREN TERHADAP PEREKONOMIAN MASYARAKAT LOKAL - Wulansari, Arta Dias; Yulistiyono, Herry (Universitas Nusantara PGRI Kediri, 2021)
This study aims to determine the respondent's perception of the economic impact of the existence of the Kemantren Tourism Village and to find out how big the economic impact of tourism activities in the Kemantren Tourism Village is on the economy of the local community. The method used is descriptive quantitative. The analytical method used is descriptive analysis and multiplier effect. The results showed that the perception of respondents stated the interpretation of